Carbonic anhydrase, its inhibitors and vascular function - García-Llorca, Andrea; Carta, Fabrizio; Supuran, Claudiu T.; Eysteinsson, Thor (Frontiers in Molecular Biosciences, 2024)
It has been known for some time that Carbonic Anhydrase (CA, EC 4.2.1.1) plays a complex role in vascular function, and in the regulation of vascular tone. Clinically employed CA inhibitors (CAIs) are used primarily to lower intraocular pressure in glaucoma, and also to affect retinal blood flow and oxygen saturation. CAIs have been shown to dilate vessels and increase blood flow in both the cerebral and ocular vasculature. Similar effects of CAIs on vascular function have been observed in the liver, brain and kidney, while vessels in abdominal muscle and the stomach are unaffected. Most of the studies on the vascular effects of CAIs have been focused on the cerebral and ocular vasculatures, and in particular the retinal vasculature, where vasodilation of its vessels, after intravenous infusion of sulfonamide-based CAIs can be easily observed and measured from the fundus of the eye. The mechanism by which CAIs exert their effects on the vasculature is still unclear, but the classic sulfonamide-based inhibitors have been found to directly dilate isolated vessel segments when applied to the extracellular fluid. Modification of the structure of CAI compounds affects their efficacy and potency as vasodilators. CAIs of the coumarin type, which generally are less effective in inhibiting the catalytically dominant isoform hCA II and unable to accept NO, have comparable vasodilatory effects as the primary sulfonamides on pre-contracted retinal arteriolar vessel segments, providing insights into which CA isoforms are involved. Alterations of the lipophilicity of CAI compounds affect their potency as vasodilators, and CAIs that are membrane impermeant do not act as vasodilators of isolated vessel segments. Experiments with CAIs, that shed light on the role of CA in the regulation of vascular tone of vessels, will be discussed in this review. The role of CA in vascular function will be discussed, with specific emphasis on findings with the effects of CA inhibitors (CAI).